Decline in the Reform of Law Teaching? The impact of policy reforms in tertiary education - Vivienne Brand (Legal Education Review)
In an article highlighting a number of problems with regard to the way in which centralised equity policy has been implemented in Australian universities, Eleanor Ramsey has noted the lack of equity programs directed at participation- based issues. In particular she comments that programs which target the content of courses, and the pedagogy of those who teach them, are rare. The rarity of such programs is connected with the fact that much of the focus of analyses of equity in curriculum has centred on secondary and primary education. As Thomas comments, “what is surprising is that so few feminist researchers in the sociology of education have chosen to look at higher education.” It has been left to the radical feminists to argue, for example, “that higher education curricula are as biased towards male experience as secondary education curricula.” Participation-based equity issues, such as curriculum issues, have also been overshadowed to date by concerns about access. In the context of tertiary legal education, however, access for women (at least white, middle-class, English speaking, city-dwelling women) is no longer a significant equity issue.6 Women students of law are not included, for example, in the table of targets for enrolled students in equity groups in the Equity Plan of the Queensland University of Technology. Five years ago women represented approximately 50% of students studying law in Australian universities. This continues to be the case at the Queensland University of Technology Faculty of Law.